2020
DOI: 10.21203/rs.3.rs-56437/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profile of parasuicide cases attending Brits Hospital, North West Province, South Africa: a 5-year chart review

Abstract: Background Parasuicide is referred to as an apparent attempt at suicide without the actual intention of killing oneself. Its prevalence continues to increase in the Brits/Madibeng community. The current study aimed to determine the profile of parasuicide cases attending Brits Hospital, North West Province of South Africa, from 2013 to 2018. Methods The basis of this article is a 5-year retrospective chart review of parasuicide cases attending Brits Hospital from 01 January 2013 to 01 January 2018. Brits Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Gender-specific differences in suicidal behaviour have been analysed in a number of studies with conflicting outcomes. 21,22,23,24,25 A number of studies addressing sex (male or female) differences in suicidal behaviour have reported no significant differences between males and females, 26 whilst others have confirmed significant relationships between suicidal behaviour and sex (male or female). 27,28,29 In a more recent study, no significant sex-based difference was evident.…”
Section: Discussionmentioning
confidence: 99%
“…Gender-specific differences in suicidal behaviour have been analysed in a number of studies with conflicting outcomes. 21,22,23,24,25 A number of studies addressing sex (male or female) differences in suicidal behaviour have reported no significant differences between males and females, 26 whilst others have confirmed significant relationships between suicidal behaviour and sex (male or female). 27,28,29 In a more recent study, no significant sex-based difference was evident.…”
Section: Discussionmentioning
confidence: 99%